Reflection on an Innovative International Partnership during the COVID-19 Pandemic - LeBeau, Ling Gao; Zhang, Fajun (Journal of International Students, 2022)
This reflective essay discusses how Southwest University (China) created an innovative international partnership initiative with universities in Australia, New Zealand, and the U.S. during the global pandemic. It articulates the context of the initiative, agreement establishment, program implementation, and lessons learned. This reflection aims to provoke deep thinking of how transformative international cooperation could help impact higher education internationalization.